A randomized controlled study of nebulized 3% saline versus 0.9% saline with adrenaline in the treatment of acute bronchiolitis - Sreenivasa, B; Kumar, P Sunil; Babu, M T Suresh; Ragavendra, K (Indian Journal of Child Health, 2015)
Objective: The objective was to determine whether nebulized hypertonic (3%) saline with adrenaline is more effective than nebulized 0.9% saline with adrenaline in the treatment of acute bronchiolitis. Materials and Methods: In this randomized, double-blind, controlled study 100 patients were randomly allocated into two groups (50 patients in each group). In Group A (normal saline group), 4 ml of normal saline (0.9%) and 1 ml of 1:1,000 adrenaline was given as nebulization with oxygen flow of 6-8 L/min. In Group B (hypertonicsaline group), 4 ml of hypertonic saline (3%) and 1 ml of 1:1,000 adrenaline was given as nebulization with oxygen flow of 6-8 L/min. The nebulization was given at an interval of 4 h, 6 times daily till the patient was ready for discharge. Results: The percentage improvement in clinical severity scores after inhalation therapy was not significant in Group A on 1st-3rd day after admission (3.4%, 2.1%, and 4%, respectively). In Group B, significant improvement was observed on these days (7.4%, 8.7%, and 9.9%, respectively, p